Contrast of Physical Fitness between Rai and Limbu Ethnic Communities of Phalelung Rural Municipality: A Comparative Analysis - Rai, Manu; Shahi, Suresh Jang (Research Journal, 2023)
This paper reports the findings of the study which attempted to compare and analyze the contrast of physical fitness between Rai and Limbu ethnic boy students of Phalelung-2 Rural Municipality, Panchthar. Drawing upon the quantitative approach, the study was based on comparative and descriptive research design. Altogether 24 boy students were selected as the sampled population using purposive non-random sampling procedure. Among them, 12 were from Rai and 12 from Limbu communities. The physical fitness test battery developed by American Association for Health, Physical Education and Recreation (AAHPER) was applied with the minor adaptation as the tool for data collection. While comparing the mean score, the boys from Rai community were found better than their counterpart group in pull-ups, shuttle-run and sit-ups. Likewise, the Limbu students were found to better than their counterpart group in standing broad jump, 50-yard dash and 600-yard run/walk. The sit-ups test has showed significant difference among six test items between two counterpart groups. It was also found that there is no significant difference in physical fitness between two counterpart groups. Whereas equating the composite score between both groups, it found no significant difference between both ethnic groups. It implies that both the ethnic groups should be treated with similar types of physical and sporting activities.